The Integration Of Financial Technology, Financial Literacy, And Self-Control In Shaping Financial Well-Being: A Behavioral Finance Approach Among Millennials - Nisa Septiani; Dina Yulia Wijaya; Riani Winarni (Journal of Business and Management Inaba, 2026)
Digital financial platforms are becoming an important part of millennials’ daily financial activities, influencing how they make transactions and manage their finances. Although fintech offers convenience and accessibility, its increasing use is also associated with consumptive behavior and impulsive financial decision-making. This research focuses on understanding how technological, cognitive, and behavioral factors contribute to financial well-being among millennials. A phenomenological qualitative design was utilized to obtain deeper insights into millennials’ financial experiences in the digital era. Data was collected through in-depth interviews with millennials who actively use fintech services such as e-wallets, pay later facilities, and digital investment platforms. Selected participants who met the research criteria were involved in the study, and thematic interpretation was utilized to understand issues connected to financial behavior and financial well-being. The study indicates that fintech utilization simplifies digital financial activities, although excessive use may stimulate impulsive spending when individuals have limited financial understanding and weak behavioral regulation. Financial literacy contributes to improving the quality of financial decision-making, Individuals with stronger self-control tend to be more capable of controlling spontaneous spending behavior. Furthermore, the study demonstrates that financial well-being is formed through the interaction among technological, cognitive, and psychological factors. Millennials who are able to balance fintech utilization with financial understanding and behavioral control tend to exhibit better financial stability and financial well-being. The research offers an integrative perspective regarding financial behavior in digital financial environments. The findings also provide practical implications for improving financial literacy and promoting responsible fintech usage among millennials.